Childhood and education: between medicalization and subjectivation processes in school - César Donizetti Pereira Leite; Rafael Christofoletti (FahrenHouse, 2018)
In this study we assessed the thematic of child's pathological process and we indicated a perspective view in which one has a series of possibilities of exercising the difference. If for some researchers this is a one-way street due to the advancement and evolution of scientific advances in Psychiatry, for others it is seen as the radicalization of the social control policy function through a process of standardization and straightening of differences. It is well known that problems of medicalization in Education has got strength in previous years. It directly involves disciplinary issues, in both sense of learning and «childish behavior». Among several factors explored in this study, we discussed the impact of the homogenization of the understanding of what learning is and the forms regarded as adequate for children behavior. In summary, this article aims (1) to problematize the «pathologization» of the education and of the child based on Michel Foucault's analysis of the psychiatric power (and its implications for thinking about human development), (2) to point a perspective in which the childhood acquires other possibilities of exercising the difference based on Gilles Deleuze's philosophy, (3) and to indicate some clues for thinking a non-medicalized education (or a pedagogy around the subjectivities).